Tanggung Jawab Kurator Keperdataan Pegawai Negeri Sipil dalam Pengurusan dan Pemberesan Harta Pailit - Evans Al Faridzi (Jurist-Diction, 2022)
AbstractBankruptcy is one of the instruments in overcoming a situation where the payment of an obligation does not run smoothly. Creditors or even debtors themselves can submit bankruptcy applications to the competent Commercial Court to examine whether they meet the requirements for determining bankruptcy status. If it meets the requirements and no objections are raised by the parties, the curator will proceed with the process of managing and clearing the bankruptcy estate. The curators are divided into state curators, namely Balai Harta Peninggalan (BHP) and private curators. In carrying out its duties as a curator, BHP shall be borne by the Civil Curator Functional Officer. The purpose of this study is to determine the location of the responsibility for the management and settlement of bankruptcy assets carried out by BHP and what sanctions can be imposed if an error occurs. Keywords: Bankruptcy; Curator; Government Employees. AbstrakKepailitan merupakan salah satu instrumen dalam mengatasi terjadinya suatu keadaan pembayaran atas kewajiban yang tidak berjalan dengan lancar. Kreditor atau bahkan debitor sendiri dapat mengajukan permohonan pailit kepada Pengadilan Niaga yang berwenang untuk diperiksa apakah sudah memenuhi persyaratan ditetapkannya status pailit. Jika memenuhi persyaratan dan tidak diajukannya keberatan oleh pihak-pihak maka dilanjutkan dengan proses pengurusan dan pemberesan harta pailit oleh kurator. Kurator terbagi menjadi kurator negeri yaitu Balai Harta Peninggalan (BHP) dan kurator swasta. BHP dalam melaksanakan tugasnya sebagai kurator dibebankan kepada Pejabat Fungsional Kurator Keperdataan. Tujuan penelitian ini untuk mengetahui letak tanggung jawab pengurusan dan pemberesan harta pailit yang dilakukan oleh BHP dan apa saja sanksi yang dapat dikenakan jika terjadi kesalahan. Kata Kunci: Kepailitan; Kurator; Pegawai Negeri Sipil.